Basic Concepts (Categories) of Sports Theory - Abbasov Baxadir Asatillayevich (Academia One Publishing, 2023)
In the process of studying the theory of sports, it is necessary, first of all, to strictly define the concepts that relate to the subject of this discipline. In this article highlights of basic concepts (categories) of sports theory
Keywords: sport; sport theory; categories; subject